MANUAL OF GOOD PRACTICES FOR FOOD BANKS: THE PERSPECTIVE OF A NEW CONSTRUCTION - Natália Ferreira de Paula; Luana de Assis; Cilene da Silva Gomes Ribeiro; Islandia Bezerra (Universidade do Estado do Rio de Janeiro, 2017)
Food Banks (FB) are the most important Food and Nutrition Security (FNS) Tools to fight against food waste all over the country. There are currently 214 FB operating in Brazil. The food received by the Banks usually have no commercial value, however, it is adequate for consumption. The Good Practices, on the other hand, become essential elements to guarantee the quality of the received and donated food by the FB. The Manual of Good Practices (MGP) guides the implementation of Good Practices and helps their maintenance. Considering the importance of the MGP for the promotion of the FNS of the recipients, as well as the lack of specific literature for the sector, this article presents a Script proposition of the MGP with an expanded view for application in FB. The systematization of the proposal follows an adaptation of the MGP used for food services and regulatory frameworks referring to Good Practices in national and international scopes. The Script was composed of ten items, which are detailed, related to the regulatory frameworks, and they approach, besides the quality control usually observed for the food services, items peculiar to the FB. Finally, it is important to highlight that the MGP should be developed according to each reality. It is also worth noting that the script alone does not promote the FNS of the recipients, since there is a need to systematically implement what is described and/or to make adaptations to ensure the quality control of food DOI: 10.12957/demetra.2017.22877